Dynamics of Ocular Surface Temperature in Rabbits During Transpalpebral Cooling (10°C) - Dorokhova, Oleksandra; Zborovska, Oleksandra; Zadorozhnyy, Oleg; Kolesnichenko, Viktoriia (Problems of Cryobiology and Cryomedicine, 2024)
The study was aimed at evaluating the dynamics of the ocular surface temperature of healthy rabbits (chinchilla breed, 10 months’ age) in the ciliary body projection during artificial transpalpebral cooling (10°C). The study was conducted in 24 rabbits (48 eyes). Developed original thermoelectric devices were used for thermometry of the ocular surface and its cooling. The initial epibulbar temperature was measured by the contact method in the ciliary body projection prior to cooling. The eye was cooled by contact through closed eyelids with a constant temperature of the cooling surface of 10°C. Local epibulbar temperature was measured during 30 minutes of cooling every 10 minutes, as well as after stopping the cold exposure for 40 minutes. The decrease in the ocular surface temperature of rabbits in the ciliary body projection during the first 10 minutes was 4.6°C and for the next 20 minutes it was only 0.7°C. A rapid recovery of epibulbar temperature by 3.9°C was observed within the first 10 minutes after cessation of cold exposure, followed by delayed warming of the ocular surface by only 0.6°C for the next 30 minutes. Transpalpebral contact controlled ocular cooling at 10°C enabled to achieve a potentially therapeutic level of hypothermia of the structures of the ocular anterior segment, which led to the prospect of using the beneficial properties of artificial local hypothermia in ophthalmology. Probl Cryobiol Cryomed 2024; 34(3):213–225